Clinical epidemiology and mortality on patients with acute respiratory distress syndrome (ARDS) in Vietnam - Chinh, Luong Quoc; Manabe, Toshie; Son, Do Ngoc; Chi, Nguyen Van; Fujikura, Yuji; Binh, Nguyen Gia; Co, Dao Xuan; Tuan, Dang Quoc; Ton, Mai Duy; Dai, Khuong Quoc; Thach, Pham The; Nagase, Hiroyuki; et al. (PloS one, 2019)
The clinical epidemiology and disease prognosis in patients with acute respiratory distress syndrome (ARDS) have not yet been fully elucidated in Vietnam. We conducted a retrospective observational study at a national tertiary hospital in Hanoi, Vietnam. Participants were adult patients (age ≥18 years) who were admitted and diagnosed with ARDS during 2015-2017. Data on patients' general and clinical conditions, radiographic findings, ventilator settings, gas exchange, and treatment methods were collected and compared between survivors and non-survivors. Risk factors for mortality were assessed using logistic regression analysis. Among 126 eligible patients with ARDS admitted to the central tertiary hospital in Vietnam, we observed high mortality (57.1%). Of the total patients, 91.3% were transferred from local hospitals with a diagnosis of severe pneumonia and then diagnosed with ARDS at the central hospital. At the time of admission, 53.2% of patients had severe ARDS, 37.3% had moderate ARDS, and 9.5% had mild ARDS. The mean (standard deviation) sequential organ failure assessment (SOFA) score was 9.5 (3.4) in non-survivors and 7.4 (3.4) in survivors (p = 0.002). Although there was no significant difference in PaO2/FiO2 on admission between non-survivors and survivors, that on day 3 after admission was significantly different (p = 0.002). Logistic regression revealed that PaO2/FiO2 on day 3 [odds ratio (OR), 1.010; 95% confidence interval (CI), 1.003-1.017], length of stay in a local hospital before admission to the central hospital (OR, 1.122; 95% CI, 1.042-1.210) due to stable condition, and SOFA score on Day 1 (OR, 0.842; 95% CI, 0.708-1.002) were independent factors in patient survival. Patients with ARDS admitted the central tertiary hospital had severe illness and high mortality. Most patients were transferred from local hospitals. Improvements in human, medical, and sociological resources in local will contribute to reducing the mortality of ARDS in Vietnam.